2019
DOI: 10.1016/j.neuropsychologia.2019.107191
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking – The overlooked method to measure cognition in neurodegeneration?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 136 publications
1
27
0
Order By: Relevance
“…To this end, humans use a repertoire of functional movements which include saccades with their ballistic dynamics, smooth tracking and small tremors (Rucci & Victor, 2015). These movements have been studied extensively in paradigms which have helped isolate their characteristics and suggested in a range of contexts that the ocular motor system is a useful window into brain function (Bueno, Sato, & Hornberger, 2019;Freedman & Foxe, 2018;Kowler, 2011;Spering & Montagnini, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, humans use a repertoire of functional movements which include saccades with their ballistic dynamics, smooth tracking and small tremors (Rucci & Victor, 2015). These movements have been studied extensively in paradigms which have helped isolate their characteristics and suggested in a range of contexts that the ocular motor system is a useful window into brain function (Bueno, Sato, & Hornberger, 2019;Freedman & Foxe, 2018;Kowler, 2011;Spering & Montagnini, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The biometrics therefore captured participants' unique ocular motor signatures. With a better theoretical understanding of the relationships between the components of such biometrics, the roles played by the separate but interconnected sensorimotor networks of brain regions such as striate and extra-striate visual cortex, middle temporal visual motion area (MT), the frontal eye fields (FEF) and the superior colliculus (SC) in generating finely controlled eye movements might be more distinctly isolated and understood (Bueno et al, 2019;Freedman & Foxe, 2018;Masson & Perrinet, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The head typically is positioned in a chinrest. Calibration can be challenging for this equipment when trial sessions are long, contact or corrective lenses are used, or there are long eye lashes [14]. Modern videography and computer algorithms can measure parameters using reflections from eye layers and appearance based techniques using facial feature recognition [15].…”
Section: Tracking Methodsmentioning
confidence: 99%
“…Eye tracking is non-invasive and little training is needed to collect eye tracking data. Prior work has shown that eye movements can be used to indicate clinically-relevant neuromotor and cognitive deficits (25)(26)(27), including those measured by ImPACT. As there is a physical link between the optic nerve and the eye (i.e., its physical connection), it stands to reason that there is also a link between increased ONSD (i.e., swelling of the optic nerve) and eye movements.…”
Section: Introductionmentioning
confidence: 99%